COMPETENCE DEVELOPMENT OF STAFF AS A COMPONENT OF PROJECT QUALITY ASSURANCE - Verbovska, L.S.; Stankovska, I.M.; Bodnar , G.F.; Mykytiuk , M.O. (The actual problems of regional economy development, 2022)
The purpose of this article is to study the search for ways to develop the competencies of project managers and staff. The article substantiates the main components of staff development, improving the competencies of staff and project manager. Different definitions of the essence of "staff development" and "competence" are analyzed, which allows us to emphasize that when choosing different forms of education, in particular, training, different types of training it is necessary to use / apply modern methods and techniques for development and improvement. The main competencies of managers are considered, which are reduced to four groups: management of goals and objectives; directing subordinates; human resource management; leadership. It is determined that taking into account and combining skills "hard skills" and "soft skills" allows you to use the acquired knowledge to perform specific tasks in the workplace in a particular professional activity. Modern and traditional models, techniques and tools of personnel management are presented, which can clearly assess the difference between approaches to managing the competence of employees in a changing environment. The proposed methods of acquiring competencies allow you to choose those competencies and methods of acquiring them that correspond to the individual characteristics of organizations. It is proved that the acquisition of competencies by a project manager allows to identify new competencies in employees, to form the need for modern analytical and behavioural skills, providing greater opportunities for management skills and flexibility, dialectical thinking, creative decision making in unusual situations. The competencies of the project manager are formed, which comes down to the fact that the project manager must have five basic skills: achieving goals; leading teams; promoting change; stakeholder management and resource management. It is substantiated that the harmonious combination of competencies helps the project manager to solve complex business processes, easily adapt to change, be an active participant in meetings, speeches at conferences, forums, and various mit-upach, form an employer brand and more. The author's definition of the term "competence" is proposed, it is the ability to perform something that requires appropriate professional skills. It has been proven that incompetent non-use by staff and project team members of their knowledge, skills, experience and skills often leads to a decrease in the effect of tasks, inefficient use of their potential and loyalty of service providers.